CSR, LOCAL EMBEDDEDNESS AND THE PERFORMANCE OF MNCs IN BRAZIL DURING THE 2008 FINANCIAL CRISIS - Correa da Cunha, Henrique; Parisotto, Iara Regina dos Santos; Carpes Dani, Andreia; Siewert, Vilmar (Revista de Negócios, 2018)
Although the effects of the financial crisis of 2008 affected companies in several industries, not all organizations were affected in the same manner. When evaluating the implications of the 2008 financial crisis for the performance of multinational subsidiaries operating in Brazil during this period it is clear that some companies were better able to overcome the challenges imposed by the crisis. One explanation for that could be related to strategies adopted by these organizations that increase local embeddedness which in turn creates a reciprocal commitment between the company and the network in a sense that it provides a mutual support during challenging moments. In that sense, in order to relate to different stakeholders needs in foreign markets, the subsidiaries of multinational companies adopt CSR and governance practices. In order to verify the implications of CSR practices to the performance of multinational subsidiaries in Brazil during the financial crisis of 2008, the present study utilizes a panel data with 110 subsidiaries of multinational companies active in Brazil during 2008, 2009 and 2010. We perform a Pairwise Granger Causality test to confirm the causal relationship between CSR practices and performance. The results indicate that regardless of the size, there is a positive relationship between CSR and the performance of these organizations during the financial crisis of 2008.